Leadership in a weak-link game - Joris Gillet; Edward Cartwright; Mark Van Vugt (University of Kent, School of Economics, 2009)
We investigate, experimentally, the effects of leadership in a four player weak-link game. A weak-link game is a coordination game with multiple Pareto-ranked Nash equilibria. Because the more efficient equilibria involve a degree of strategic uncertainty groups typically find it difficult to coordinate on more efficient equilibria. Previous studies have shown that leadership by example - in the form of one player acting publicly before the rest of the group - can lead to increased cooperation in collective action problems and we are interested in finding out whether this result extends to weak-link games. Our results suggest that leadership does indeed increase coordination and efficiency. In particular, with leadership we typically observe efficiency rising over time while without it declines over time. There doesn't appear to be a difference between voluntary leaders and leaders that are (randomly) appointed.
Keywords: C72; H41; 330; weak-link game; coordination; leadership; Führungsstil; Öffentliches Gut; Koordination; Spieltheorie